2019
DOI: 10.3390/polym11101721
|View full text |Cite
|
Sign up to set email alerts
|

Tough Polyelectrolyte Hydrogels with Antimicrobial Property via Incorporation of Natural Multivalent Phytic Acid

Abstract: Tough and antimicrobial dual-crosslinked poly((trimethylamino)ethyl methacrylate chloride)-phytic acid hydrogel (pTMAEMA-PA) has been synthesized by adding a chemical crosslinker and docking a physical crosslinker of multivalent phytic acid into a cationic polyelectrolyte network. By increasing the loading concentration of PA, the tough hydrogel exhibits compressive stress of >1 MPa, along with high elasticity and fatigue-resistant properties. The enhanced mechanical properties of pTMAEMA-PA stem from the mult… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…Here the re-entrant swelling was induced by the thiocyanate ion, but not by chloride, acetate or perchlorate ions [57]. The reswelling of polyelectrolyte gels in monovalent salts has also been observed experimentally in the presence of LiCl (Figure 2d) [64] and NaCl [65] and has also been shown in theoretical work that includes the effect of ion-ion correlations [43].…”
Section: The Influence Of Monovalent Electrolytes On Polyelectrolyte ...supporting
confidence: 61%
“…Here the re-entrant swelling was induced by the thiocyanate ion, but not by chloride, acetate or perchlorate ions [57]. The reswelling of polyelectrolyte gels in monovalent salts has also been observed experimentally in the presence of LiCl (Figure 2d) [64] and NaCl [65] and has also been shown in theoretical work that includes the effect of ion-ion correlations [43].…”
Section: The Influence Of Monovalent Electrolytes On Polyelectrolyte ...supporting
confidence: 61%
“…The compression could be repeated several times without showing any damage to the samples. P­(Glu- co -Lys), on the other hand, recovered only to 83.8% of its original height and shows a pronounced hysteresis probably due to a reversible disassembly and reassembly of the physical cross-links. , This effect is more pronounced at slower loading and unloading rates as this gave the physical network more time to rearrange. On the other hand, P­(Glu- co -Lys) shows a similar unloading behavior as P­(Glu) and P­(Glu- co -Phe) when a higher compression rate is used.…”
Section: Resultsmentioning
confidence: 82%
“…The effect of IP6 on the characteristics of polyelectrolyte hydrogel, a tissue engineering scaffold, was studied. It was concluded that IP6 produced a hydrogel scaffold with improved mechanical properties and antimicrobial capability (Bui and Huang, 2019). Several other researchers reported enhanced characteristics of biocements with the use of IP6; however, its effect on the setting time is dependent on several factors that are beyond the scope of this review (Horiguchi et al, 2008;Konishi et al, 2012;Christel et al, 2015;Medvecky et al, 2020).…”
Section: Regenerationmentioning
confidence: 89%